Comparison of macular choroidal thicknesses from swept source and spectral domain optical coherence tomography. Issue 7 (9th November 2015) - Tan, Colin S; Cheong, Kai Xiong; Lim, Louis W; Sadda, SriniVas R
Abstract : Background: Choroidal thickness (CT) measurements differ between swept source optical coherence tomography (SS-OCT) and spectral domain OCT (SD-OCT) devices for point thickness measurements. We aimed to assess the comparability of mean macular CT measurements between SS-OCT and SD-OCT devices. Methods: In a prospective cohort study of 25 healthy volunteers, OCT scans were performed sequentially with the deep range imaging (DRI) OCT-1 and Spectralis OCT using standardised imaging protocols. These OCT scans were independently graded by reading centre-certified graders to obtain mean CT in the various Early Treatment Diabetic Retinopathy Study (ETDRS) subfields. Paired t tests and intraclass correlation coefficients (ICCs) were used to compare the measurements. Results: The difference in mean central subfield CT between DRI OCT-1 and Spectralis was 49.3 µm (p<0.001), while differences in CT in various ETDRS subfields varied from 42.1 to 67.2 µm. After manual adjustment of the segmentation boundaries for the central subfield in the DRI OCT-1, the mean central subfield CT for DRI OCT-1 increased from 263.1 to 293.3 µm (p<0.001), and the resultant difference between DRI OCT-1 and Spectralis decreased from 49.3 to 19.1 µm (a decrease of 61.3%; p<0.001). CT between the three-dimensional and radial scanning protocols of the DRI OCT-1 were highly comparable, with differences generally under 10 µm and ICC of 0.888 for the central subfield. Conclusions: CT measurements between automated segmentations from the DRI OCT-1 and manual segmentations on the Spectralis OCT may differ by more than 50 µm. This difference can be reduced, but not eliminated, by manual adjustment of segmentation boundaries by trained graders, and should be accounted for when comparing results between the two devices.